Preparedness of KSOP officers in preventing and managing ship-generated waste under MARPOL 73/78 Annex V: A case study of Tanjung Perak Main Port, Indonesia - Putra, Achmad Rangga Dwi Hariansyah; Radiansyah, Muhammad Dimas; Muttaqin, Andik Dwi (Journal of Marine Resources and Coastal Management, 2025)
Marine pollution from ship waste poses a significant threat to global and national ecosystems, particularly in Indonesia, the world’s largest archipelagic country with 5.8 million km² of waters. This study examines the preparedness of officers at the Tanjung Perak Harbormaster and Port Authority Office (KSOP) in preventing and managing ship waste according to MARPOL 73/78 Annex V, using a mixed-methods descriptive qualitative-quantitative approach. Data were collected through semi-structured interviews, participant observation, document studies, and surveys of 20 officers with at least two years of experience. Validity and reliability were confirmed via Content Validity Ratio (CVR) and Cronbach’s Alpha (α = 0.82). Preparedness was assessed across four dimensions, i.e., regulatory knowledge, information systems & early warning, operational response, and mobilization & equipment, yielding an overall score of 75.27% (“Ready”). Officers’ strengths were in operational response (82.5%) and equipment mobilization (83.6%), supported by 100% participation in Garbage Spill Drill simulations and boom/skimmer availability up to 95%. Weaknesses included regulatory knowledge (67.2%), particularly technical aspects of food waste management (accuracy 60–65%), and information systems (67.8%), with InaPortNet integration only 60%, reflecting global systemic deficiencies (e.g., 22.07% of MARPOL violations). Case studies of KM Sinabung, KM Dharma Ferry V, and KM Dharma Kencana V inspections showed compliance potential via Garbage Management Plans but were limited by inadequate inter-agency coordination and reception facilities (35%). The study recommends intensive training, cross-sector collaboration with Pelindo and waste contractors, and investment in digital technologies, including full InaPortNet integration and AI-based early warning systems, to achieve “Very Ready” status (≥80%). Periodic post-intervention evaluations and econometric impact analyses are also advised to optimize ship waste pollution prevention, support maritime sustainability, and advance SDG 14 on life below water.